A snapshot of online learners: e-Readiness, e-Satisfaction and expectations - Hale Ilgaz (Athabasca University Press, 2015)
The popularity of online programs that educational institutions offer is continuously increasing at varying degrees, with the major demand coming from adult learners who have no opportunity to access traditional education. These adult learners have to be sufficiently ready and competent for online learning, and have their own varied expectations from the online learning process. Hence, this mixed method study is conducted to explore the participants’ readiness and expectations at the beginning and their satisfaction levels at the end of an online learning experience. An e-readiness scale and an e-satisfaction scale was administered as quantitative measures, with open-ended questions gathering qualitative data. Participants of the research were registered to different e-learning programs at Ankara University Distance Education Center, Turkey, during the 2013-2014 academic year. Analysis of both quantitative and qualitative data revealed facts about online learners, which should prove useful to both e-instructors and e-program administrators.